A robust and miniaturized screening platform to study natural products affecting metabolism and survival in Caenorhabditis elegans - Julia Zwirchmayr (Nature Portfolio, 2020)
Abstract In this study a robust, whole organism screening based on Caenorhabditis elegans is presented for the discovery of natural products (NP) with beneficial effects against obesity and age-related diseases. Several parameters of the elaborated workflow were optimized to be adapted for probing multicomponent mixtures combining knowledge from traditional medicine and NP chemistry by generating optimized small-scale extracts considering scarcity of the natural source, solubility issues, and potential assay interferences. The established miniaturized assay protocol allows for in vivo probing of small amounts of even complex samples (~ 1 mg) to test their ability to increase the nematodes’ survival time and the suppression of fat accumulation assessed by Nile red staining as hall marks of “healthy aging”. The workflow was applied on 24 herbal and fungal materials traditionally used against symptoms of the metabolic syndrome and revealed promising results for the extracts of Gardenia jasminoides fruits and the sclerotia from Inonotus obliquus. Tested at 100 µg/mL they were able to significantly reduce the Nile red fluorescence and extend the 50% survival rate (DT50) compared to the control groups. This phenotype-directed in vivo approach opens up new horizons for the selection of natural starting materials and the investigation of their active principles as fast drug discovery tool with predictive value for human diseases.